2021
DOI: 10.5397/cise.2021.00423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of bending versus non-bending of the plate hook in acromioclavicular joint dislocation

Abstract: Background: We aimed to assess the effect of plate hook bending in treatment of acromioclavicular (AC) dislocation by analyzing clinical and radiological results according to the angle of the plate hook (APH).Methods: This was a retrospective, observational, case-control study including 76 patients with acute AC joint dislocation that were divided into two groups according to treatment with bent or unbent plate hook. The visual analog scale (VAS), the American Shoulder and Elbow Surgeons (ASES) shoulder score,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(22 reference statements)
3
5
0
Order By: Relevance
“…As part of this effort, studies have also been reported on whether the angle of the hook part is 90 degrees or whether a larger angle is appropriate. As a result, it was reported that a hook angle of 105 degrees or 110 degrees is appropriate to reduce the complications related to the hook [29][30][31]. Yoon et al reported that the hook made a pin-point contact with the undersurface of the acromion, and the force concentration phenomenon associated with the hook plate of existing designs results from cases of morphological mismatch, such as excessive inclination and improper occupation of the subacromial space [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this effort, studies have also been reported on whether the angle of the hook part is 90 degrees or whether a larger angle is appropriate. As a result, it was reported that a hook angle of 105 degrees or 110 degrees is appropriate to reduce the complications related to the hook [29][30][31]. Yoon et al reported that the hook made a pin-point contact with the undersurface of the acromion, and the force concentration phenomenon associated with the hook plate of existing designs results from cases of morphological mismatch, such as excessive inclination and improper occupation of the subacromial space [45].…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies, the authors emphasized the complications can be minimized by performing an anatomic fit of the plate during the procedure and found it necessary to bend the hook [14,27,28]. Precontouring of 20 degrees in the VariAx lateral hook plate is thought to be influenced or reflect these previous research results [29][30][31]. In order to match the hook part of the metal plate with the lower edge of the acromion as much as possible, the special fluoroscopic view technique we developed was utilized for the best fit between the hook and the acromion, which was helpful in reducing the inevitable acromial erosion [27].…”
Section: Methodsmentioning
confidence: 99%
“…One of them is subacromial erosion/osteolysis due to use of a plate hook [4,5]. The study, "The clinical outcomes of bending versus non-bending of the plate hook in acromioclavicular joint dislocation, " by Joo et al [6] in the issue focuses on subacromial osteolysis of the hook plate and its associated deterioration of clinical outcomes. Several papers have demonstrated that friction pain and osteolysis are caused by compression of the subacromial area of the hook plate [7][8][9][10].…”
mentioning
confidence: 99%
“…In a study by Joo et al [6], the hook plate was bent with the angle of the plate hook an average of 21°, and patient outcomes were compared with those of the non-bending group. The results showed that the incidence of subacromial osteolysis was significantly reduced, and the clinical outcome prior to plate removal had improved considerably.…”
mentioning
confidence: 99%
See 1 more Smart Citation